The Idea of the Intellectual Tradition of Shaykh Nawawi: an in -Depth Analysis in the Context of Thought and Contribution to Islamic Studies - Saepul Bahri; M.A Tihami; Umi Kultsum (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to provide a profound analysis of the intellectual tradition of Sheikh Nawawi and explore his contributions in the context of Islamic thought. With a focus on key aspects such as interpretative methodology, the interpretation of classical texts, and philosophical thinking, this research unveils the profound dimensions of Sheikh Nawawi's thought that transcend the boundaries of traditional disciplines. Through a holistic approach, the article details Sheikh Nawawi's central role in the development of knowledge while highlighting its impact in the fields of Islamic theology and philosophy. This analysis not only strengthens the understanding of his intellectual work but also evaluates the relevance of his contributions in contemporary contexts, offering valuable insights into the integration of classical intellectual traditions and contemporary challenges in Islamic studies.